The effect of exercises according to the target time of the equation (Touchdown) on partial distances, skillful performance and achievement in 400 meters hurdles’advanced runners - Jawad, AlaaFlayyih; Hasan AbdalRedha, Ammar; SattarJaber, Imad (International Journal of Psychosocial Rehabilitation, 2020)
The goal of sports training is the number of athletes to achieve the best achievement in efficiency specialist through exercises that apply training programs in accordance with the methods and methods of sports training and by energy systems, and is the effectiveness of the enemy (400 m hurdles), One of the events that require highly trained and the most important requirements are high performance The ideal is to pass the barriers (skill performance) and the enemy from the starting line to the first barrier and the enemy between the barriers with a smooth flow and an ideal distribution of effort and what this distribution requires of high physical capabilities that are compatible with the physical, physiological and skill abilities and capabilities of the runners during training or competition and the enemy from the tenth barrier to the finish line, to achieve the best achievement of the enemy effectively, so headed researcher Wen to develop this Almngara through the use of exercises according to the target time to equate (Touchdown), And to identify the impact of the partial distances and skillful performance and achievement of hostile (400 m hurdles) applicants, as well as to identify the advantage of these exercises for exercises adopted by trainers in the development of the variables under study and the completion of the effectiveness run (400 m hurdles), and the researcher used the One experimental approach in a manner the experimental and control groups Almtkavitin chose to sample his research m from the clubs of Karbala in a way comprehensive inventory was the most important research procedures determine partial distances and determine the measurement of research variables, and used statistical methods parametric arithmetic mean, standard deviation and the law of Levin and the law (T) for symmetric and independent samples of equal number to find differences between the pre- and post-tests and between the post-tests between the experimental and control groups, and among the most important conclusions, the exercises contributed according to the target time to equation Touchdown (in developing the variables under study and giving runners the ideal distribution of physical effort exerted, whether in competition or training, and thus improving achievement, and the preference of these exercises over the exercises used by trainers, and the most important recommendations are the adoption of exercises according to the target time to equalize) Touchdown In the development of the variables under study and the achievement of running (400 meters hurdles) and the need to  pay attention to it by the trainers and those concerned with the specialty, and to emphasize the skillful aspect of overcoming barriers, and to apply these exercises to other activities and to different groups.